2015
DOI: 10.1155/2015/731319
|View full text |Cite
|
Sign up to set email alerts
|

The Duration of Breastfeeding and Its Association with Metabolic Syndrome among Obese Children

Abstract: Objective. The objective of this study was to evaluate whether duration of breastfeeding is associated with a lower prevalence of metabolic syndrome in obese children. Methods. A retrospective analysis of obese children aged 3 to 18 years followed at a pediatric outpatient clinic at a single center between the years 2008 and 2012. The children were divided according to their breastfeeding duration: no breastfeeding, a short period of breastfeeding, and a long term breastfeeding. Also, they were divided into me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…These findings suggest the potentially positive effect of breastfeeding as a way to prevent the development of metabolic disorders in young subjects. These results contrasted with Yakubov et al [24], who found no association between breastfeeding duration and the development of MetS and/or impairments of its components. However, this lack of association could be explained by factors such as the small size of the sample, a possible selection bias of the subjects or the range of breastfeeding duration.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings suggest the potentially positive effect of breastfeeding as a way to prevent the development of metabolic disorders in young subjects. These results contrasted with Yakubov et al [24], who found no association between breastfeeding duration and the development of MetS and/or impairments of its components. However, this lack of association could be explained by factors such as the small size of the sample, a possible selection bias of the subjects or the range of breastfeeding duration.…”
Section: Discussioncontrasting
confidence: 99%
“…Both of these studies did a follow-up analysis comparing those who completed the study with those who did not, and Martin et al (2014) also completed a sensitivity analysis. The third cohort study failed to mention follow-up rates (Yakubov, Nadir, Stein, & Klein-Kremer, 2015). Misclassification (misdiagnosis) of metabolic syndrome was also a potential source of bias because most articles failed to collect disease history (e.g., diabetes, lipid abnormalities, or hypertension) (Esfarjani, Khalafi, Mohammadi, Zamani-Nour, & Kelishadi, 2013; González-Jiménez, Montero-Alonso, Schmidt-RioValle, García-García, & Padez, 2015; Figure 2.…”
Section: Quality Assessment Resultsmentioning
confidence: 99%
“…Jamoussi et al, 2012;Khuc et al, 2012;S. Wang et al, 2015;Yakubov et al, 2015) that may have improved the ability of the researchers to correctly identify metabolic syndrome. For instance, if a child/adolescent was previously diagnosed with type 2 diabetes but his or her glucose levels were measured as normal at the time of study outcome ascertainment, he or she would still meet the requirement for abnormal glucose levels if disease history was considered.…”
Section: Quality Assessment Resultsmentioning
confidence: 99%
“…However, research on the association between BF and lower risk of diabetes and MetS is limited in offspring of mothers with GDM . In addition, research suggests that BF may decrease the prevalence of MetS, although not all findings are consistent …”
Section: Introductionmentioning
confidence: 99%
“…31 In addition, research suggests that BF may decrease the prevalence of MetS, although not all findings are consistent. 32,33 To date, no study has examined the association between BF and GDM status on prevalence of MetS and prediabetes in young children, particularly in a high-risk Hispanic population. Therefore, this study aims to assess the effects of BF and GDM on the prevalence of MetS and prediabetes in Hispanic children and adolescents as they age (8-19 y).…”
mentioning
confidence: 99%